Hubungan Kelompok Usia Terhadap Kadar Glukosa Darah Sebelum dan Sesudah Senam Pada Lansia Paguyuban Triyagan - Oktavia, Khaila Adinda; Adi, Omry Tri Asmara (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Elderly people experience a decline in physiological functions that affect glucose metabolism, putting them at risk of unstable blood glucose levels. Physical activity such as morning exercise is an effective non-pharmacological intervention to help lower blood glucose levels by increasing insulin sensitivity and glucose utilization by muscles. This study aims to determine the relationship between age groups and blood glucose levels before and after morning exercise in the elderly at Paguyuban Triyagan, Sukoharjo. The study used a pre-post test design with a quantitative approach. The sample consisted of elderly aged ≥60 years who participated in morning exercise activities, divided into two age groups: young elderly (60–69 years) and elderly elderly (≥70 years). Blood glucose levels were measured before and after exercise for ±30 minutes. The Wilcoxon Signed Rank Test showed a significant difference between blood glucose levels before and after exercise (p = 0.028), which means that morning exercise lowers blood glucose levels. However, the results of the Independent Sample T-test (p = 0.763) showed no significant difference between the two age groups. In conclusion, morning exercise is effective in reducing blood glucose levels in the elderly without being influenced by age factors, so it can be recommended as a routine activity to maintain the metabolic health of the elderly.